IDENTIFIKASI PROSES BERPIKIR SISWA DALAM MENYELESAIKAN PERTANYAAN PADA MATERI BIOLOGI - Prasetiyo Prasetiyo (Bioma : Jurnal Ilmiah Biologi, 2015)
The quality of Human Resources always be improved, one of theimprovement is through the education, which is adjusted curriculumto be more up to date. It could be seen from behind the 2013?óÔé¼Ôäóscurriculum. This research?óÔé¼Ôäós aim was to determined the way ofstudent?óÔé¼Ôäós answering questions in biological material. The methodused was a qualitative method in one of the SMK in Semarang, classX. The results showed the students use Thinking Conceptual 30 %,Semi Conceptual 70 % and Computational 0 %. The conclusion ofthis research was the majority of students used Semi Conceptualthinking process.Keywords: thinking process, conceptual, semi-conceptual,computational